FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KOPERASI NELAYAN DALAM UPAYA PENINGKATAN KESEJAHTERAAN ANGGOTANYA - Slamet Subari (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2012)
ABSTRACTThe fishermen cooperativeis as part of the institutional system of the local economy of coastal communities, its role is expected to make corrections to the economic injustices there. As a joint venture container for fishermen, cooperatives should be able to be